2014
DOI: 10.1177/0897190014550718
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With Medication Therapy Management Services at a University Ambulatory Care Clinic

Abstract: A survey was issued to patients enrolled in the Medication Therapy Management Clinic (MTMC) at University of Illinois Hospital and Health Sciences (June 2011-January 2012) in order to assess satisfaction with pharmacy services provided by pharmacists. A 23-item survey was offered to 65 patients in the MTMC program before or after clinic visits. Since there is a paucity of data indicating the level of satisfaction with MTM services provided by pharmacists, this survey may contribute to the process of building a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Patient-perceived pharmacist expertise was described as an independent factor of patient satisfaction 10. Kim et al 9 assessed satisfaction with pharmacy services provided though medication therapy management. Patient satisfaction was not significantly different according to age, gender, ethnicity or number of disease states but, satisfaction with the medication therapy management correlated positively with overall patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-perceived pharmacist expertise was described as an independent factor of patient satisfaction 10. Kim et al 9 assessed satisfaction with pharmacy services provided though medication therapy management. Patient satisfaction was not significantly different according to age, gender, ethnicity or number of disease states but, satisfaction with the medication therapy management correlated positively with overall patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Although pharmacist services have been implemented in a variety of hepatology settings, there is a dearth of data on patient satisfaction with clinical pharmacist services in this specialty. However, patient satisfaction with clinical pharmacist services has been evaluated in the medication therapy management (MTM) clinic setting . As the clinical pharmacist's role continues to evolve beyond MTM and into specialty clinic settings such as hepatology, it is important to assess patient satisfaction with clinical pharmacist interventions in other clinic settings.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…However, patient satisfaction with clinical pharmacist services has been evaluated in the medication therapy management (MTM) clinic setting. 8,9 As the clinical pharmacist's role continues to evolve beyond MTM and into specialty clinic settings such as hepatology, it is important to assess patient satisfaction with clinical pharmacist interventions in other clinic settings.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…5,6 The overall themes of this study point to a positive impact on primary care provider experience. Other studies have highlighted a positive impact on cost 6,8 and patient experience, 7,8 the final 2 components of the Quadruple Aim. Thus, there is a potential opportunity to facilitate expansion of CMM through preparing both primary care providers and pharmacists to frame the value equation of CMM away from the basic accounting principles of feefor-service to one that takes into account positive benefits across the dimensions of health care quality, costs, patient experience and provider work-life.…”
Section: Discussionmentioning
confidence: 99%
“…2 CMM is a defined process of care most often provided by a pharmacist and can take place in many settings, including primary care practices. 3 Research has demonstrated that CMM contributes to the Triple Aim-a goal that originated with the Institute for Healthcare Improvement, 4 and is now endorsed by many organizations-by improving patients' health, 5,6 enhancing patients' care experience, 7,8 and decreasing health care costs. 6,8 In recent years, the Triple Aim has been extended to a Quadruple Aim with a new goal added to "improve the work-life of health care providers."…”
mentioning
confidence: 99%